Ocular Manifestation of Monkeypox: A Systematic Reviews: Poster Presentation - Systematic Review - General practitioner - dr. Wilson Christianto Khudrati; Dr. Titiek Ernawati, dr., SpM; dr. Kevin Anggakusuma Hendrawan (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : On July 23, 2022, the World Health Organization declared the monkeypox epidemic a global public health emergency. The majority of clinical studies on monkeypox have concentrated on its dermatological symptoms, but mounting data raises questions regarding its ocular side effects. Methods : Thirteen studies were found among the 541 distinct articles that were evaluated. Overall, ten studies were case reports, two studies of case series, and one observational cohort study. Ocular manifestations of monkeypox were vesicopapular lesions on the eyelid and conjunctiva, conjunctivitis, epiphora, photophobia, foreign body sensation, eye edema, vision changes, eye pain, itchy eyes, eye discharge, bilateral eye involvement, corneal involvement, keratitis, and subconjunctival nodules. Results : The most prevalent ocular symptoms of monkeypox were conjunctivitis, followed by eye pain and photophobia. It is still unknown whether the ocular involvement is due to self-inoculation or the systemic transmission of the virus during the early viral phase of the illness. Despite some theories involving the transit of monkeypox into the conjunctival secretions via the plasma compartment, this study also showed that conjunctival swab PCR is 100% positive, equal to skin lesion swabs. Conclusion : In conclusion, to the best of our knowledge, this is the first review with a larger sample and the newest study to report the ocular manifestations of monkeypox disease. The primary ocular symptoms were conjunctivitis, eye pain, and photophobia. In addition, it is advised that healthcare professionals, especially ophthalmologists, use eye protection goggles when close to patients.